Object-oriented and classical software engineering - Schach, Stephen R. author (New York : McGraw-Hill, 2011)
Using detailed case studies to show the object-oriented approach to software engineering, Object-Oriented and Classical Software Engineering, Eighth Edition presents an excellent introduction to software engineering fundamentals. The book covers both traditional and object-oriented techniques.
While maintaining a unique organization with Part I covering the underlying software engineering theory, and Part II presenting the more practical software life cycle, the eighth edition includes significant revisions to problems, new content, as well as a new chapter to enable instructors to better utilize the book in a one-semester course. Complementing this well-balanced approach is the straightforward, student-friendly writing style, through which difficult concepts are presented in a clear, understandable manner.
The website accompanying the text features complete Java and C++ implementations of the MSG Foundation case study, developed using the Unified Process. The site also includes lecture PowerPoint{u0CEC}ides, an image library, and an instructor's solutions manual. --Book Jacket.
The scope of software engineering -- Software life-cycle models -- The software process -- Teams -- The tools of the trade -- Testing -- From modules to objects -- Reusability and portability -- Planning and estimating -- Key material from Part A -- Requirements -- Classical analysis -- Object-oriented analysis -- Design -- Implementation -- Postdelivery maintenance -- More on UML -- Emerging technologies -- Appendix A: Term project : Chocoholics Anonymous -- Appendix B: Software engineering resources -- Appendix C: Requirements workflow : the MSG Foundation case study -- Appendix D: Structured systems analysis : the MSG Foundation case study -- Appendix E: Analysis workflow : the MSG Foundation case study -- Appendix F: Software project management plan : the MSG Foundation case study -- Appendix G: Design workflow : the MSG Foundation case study -- Appendix H: Implementation workflow : the MSG Foundation case study (C++ version) -- Appendix I: Implementation workflow : the MSG Foundation case study (Java version) -- Appendix J: Test workflow : the MSG Foundation case study.
Includes bibliographical references and indexes.
Buku bacaan asas fakulti
Keywords: Software engineering; Object-oriented programming (Computer science).; UML (Computer science).; C++ (Computer program language